Conceptual framework for public governance of socio-economic systems: from instrumental to substantional understanding of digital transformation - Sikalo , Maksym (Pressing Problems of Public Administration, 2025)
This paper examines the phenomenon of digital transformation in socio-economic systems as an object of public governance through the transition from an instrumental to a substantional understanding of digital technologies’ role. Using an interdisciplinary approach, the research systematizes theoretical and methodological concepts of digital transformation and identifies its seven fundamental properties: transversality, recursiveness, emergence, accelerativity, cognitive-transformational potential, institutional reconfigurability, and ontological hybridity. These properties form the methodological foundation for a new understanding of digital transformation, where technologies are viewed not as external optimization tools but as constitutive elements of a new institutional reality. The study develops a matrix of digital transformation’s impact on components of the socio-economic system, structuring the nature of changes, influence mechanisms, and resulting effects for economic, social, political-administrative, innovative, and informational subsystems. The research analyzes the evolution of public governance instruments for digitalization—from e-government to digital statehood models focused on digital resilience and platform-based approaches. Based on analysis of real-world cases of public sector digital modernization across different countries, the study confirms that effective public governance of digital transformation requires a comprehensive approach that accounts for the systemic nature of transformational processes. The research demonstrates that the transitive model of digital statehood creates a methodological foundation for proactive responses to digital era challenges through vertical integration of artificial intelligence systems and distributed ledgers into mechanisms of strategic planning and institutional adaptation.